2016
DOI: 10.1158/1538-7445.sabcs15-p2-11-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P2-11-01: Final pre-specified analysis of the phase II trial of the GP2+GM-CSF peptide vaccine in high risk breast cancer patients to prevent recurrence

Abstract: Introduction: We are conducting a phase II clinical trial of the GP2+GM-CSF vaccine for the prevention of breast cancer recurrence in disease-free, node-positive or high-risk node negative patients (pts). GP2 is an HLA-A2+-restricted immunogenic peptide from the HER2 protein (aa: 654-662) capable of stimulating CD8+ cytotoxic T-lymphocytes (CTLs) to recognize and destroy HER2-expressing tumor cells. Here, we present the final pre-specified analysis of our study, disease free survival (DFS) at one year from las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The vaccine was found to be safe and well tolerated, and demonstrated benefits in patients with HER2 non-over expressing tumours, especially those with triple negative disease, where the 5-year relative risk reduction for recurrence reached 35%. In a separate sub study conducted in our laboratory, we found that pre-existing immunity either as in vitro (levels of IFNγ) or in vivo (dermal reaction) parameter, might serve as a predictive biomarker for clinical response in patients vaccinated with AE37 [74][75][76]. …”
Section: The Ae37 Therapeutic Cancer Vaccine Paradigmmentioning
confidence: 92%
“…The vaccine was found to be safe and well tolerated, and demonstrated benefits in patients with HER2 non-over expressing tumours, especially those with triple negative disease, where the 5-year relative risk reduction for recurrence reached 35%. In a separate sub study conducted in our laboratory, we found that pre-existing immunity either as in vitro (levels of IFNγ) or in vivo (dermal reaction) parameter, might serve as a predictive biomarker for clinical response in patients vaccinated with AE37 [74][75][76]. …”
Section: The Ae37 Therapeutic Cancer Vaccine Paradigmmentioning
confidence: 92%